2022
DOI: 10.3389/fevo.2022.864728
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Altitude on Volatile Organic and Phenolic Compounds of Artemisia brevifolia Wall ex Dc. From the Western Himalayas

Abstract: Adaptation to changing environmental conditions is a driver of plant diversification. Elevational gradients offer a unique opportunity for investigating adaptation to a range of climatic conditions. The use of specialized metabolites as volatile and phenolic compounds is a major adaptation in plants, affecting their reproductive success and survival by attracting pollinators and protecting themselves from herbivores and other stressors. The wormseed Artemisia brevifolia can be found across multiple elevations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…The opposite trend of accumulation of phenolic compounds, depending on the elevation, was found in Vaccinium myrtillus L. both for groups of compounds and for part of plants [ 36 , 37 ]. Nataraj et al [ 38 ] reported that the concentration of phenolic compounds decreased in the leaves of Artemisia brevifolia Wall ex DC. with increased elevation.…”
Section: Discussionmentioning
confidence: 99%
“…The opposite trend of accumulation of phenolic compounds, depending on the elevation, was found in Vaccinium myrtillus L. both for groups of compounds and for part of plants [ 36 , 37 ]. Nataraj et al [ 38 ] reported that the concentration of phenolic compounds decreased in the leaves of Artemisia brevifolia Wall ex DC. with increased elevation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the alcohol–water mixture showed synergistic effects for the extraction of phenolics and flavonoids in several studies [ 21 , 22 ]. In the literature, different levels of the total phenolic and flavonoid content have been reported for the species of the genus Artemisia [ 23 , 24 , 25 , 26 ]. However, the results of spectrophotometric assays are very controversial since not only phenolic/flavonoid compounds but also other phytochemicals (peptides, sulfides, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…These compounds may play an important role in how plants cope with harsh environmental conditions along the gradient. For example, monoterpenes concentrations in Artemisia brevifolia increase with elevation (Nataraj et al, 2022 ) and have been previously suggested to play a role in plant's acclimation to high UV radiation (Nikolić et al, 2011 ). Similarly, certain monoterpenes, namely eucalyptol, camphor, and alpha/beta‐thujone accumulate under drought stress (Nowak et al, 2010 ) which tends to be a common stressor at high‐elevation sites of the Chilean Andes.…”
Section: Discussionmentioning
confidence: 99%